2011
DOI: 10.1021/ja109923a
|View full text |Cite
|
Sign up to set email alerts
|

O2 Activation by Bis(imino)pyridine Iron(II)−Thiolate Complexes

Abstract: The new iron(II)-thiolate complexes [(iPrBIP)FeII(SPh)(Cl)] (1) and [(iPrBIP)FeII(SPh)(OTf)] (2) (BIP = bis(iminopyridine)) were prepared as models for cysteine dioxygenase (CDO), which converts Cys to Cys-SO2H at a (His)3FeII center. Reaction of 1 and 2 with O2 leads to Fe-oxygenation and S-oxygenation, respectively. For 1 + O2, the spectroscopic and reactivity data, including 18O isotope studies, are consistent with an assignment of an iron(IV)-oxo complex as the product of oxygenation ([(iPrBIP)FeIV(O)(Cl)]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
116
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(129 citation statements)
references
References 45 publications
9
116
0
4
Order By: Relevance
“…[166] Substitution of triflate counter anion with different pyridines impacted the reactivity only modestly. [165] Later,i n2 011, [167] the authors demonstrated that the oxidation does not require the thiolate to be covalently anchored on the ligand. Intermediate I was characterizedb ym ass spectrometry/isotopic substitution analysis.T his species was able to readily transfer its O-atomt oP h 3 Pg enerating Ph 3 PO,a nd to exchange the oxygen with water.…”
Section: Other Imine-based Iron Complexesmentioning
confidence: 99%
“…[166] Substitution of triflate counter anion with different pyridines impacted the reactivity only modestly. [165] Later,i n2 011, [167] the authors demonstrated that the oxidation does not require the thiolate to be covalently anchored on the ligand. Intermediate I was characterizedb ym ass spectrometry/isotopic substitution analysis.T his species was able to readily transfer its O-atomt oP h 3 Pg enerating Ph 3 PO,a nd to exchange the oxygen with water.…”
Section: Other Imine-based Iron Complexesmentioning
confidence: 99%
“…[6] Beyond that, model studies with cyclam iron thiolate complexes and peracids as the oxidant are noteworthy: they showed, again in 2010, that an iron(IV) oxo intermediate [4h] is plausible in the catalytic mechanism of the CDO. [7] Herein we present the successful coordination and dioxygenation of a protected cysteinato ligand to a (His) 3 Fe II analogue and thus the most realistic biomimetic model system to date for the CDO.…”
mentioning
confidence: 99%
“…[13] The geometry of the iron centre in 5 is approximately octahedral, with the aqua ligand and one of the triflate ligands occupying "axial" positions, i. e., perpendicular to the main coordination plane defined by the three N atoms of the BIP ligand and the second triflate group. This configuration contrasts with that preferred by the analogous manganese complex [Mn(OTf) 2 (OH 2 )( Me2 BIP)], which shows both triflate groups in the axis and the aqua ligand sharing the equatorial plane with the BIP ligand.…”
Section: Resultsmentioning
confidence: 99%